Ghana : Poverty Reduction Strategy Paper-Volume II. (IMF Staff Country Reports; Country Report ;, 2012)
This volume discusses the Poverty Reduction Strategy (GPRS I) and the Growth and Poverty Reduction Strategy (GPRS II) that addressed the critical poverty issues in Ghana. GPRS I is a comprehensive policy document prepared as a precondition for Ghana under the Highly Indebted Poor Country (HIPC) Initiative. The main component-human development-targets improvement for Ghana's population to access basic needs and essential services. A general assessment shows that Ghana has a positive and significantly stabilized macroeconomic environment.